Anthocyanin-rich mulberry fruit improves insulin resistance and protects hepatocytes against oxidative stress during hyperglycemia by regulating AMPK/ACC/mTOR pathway. (March 2017) - Yan, Fujie; Zheng, Xiaodong
Highlights: MAE protects cells from oxidative stress in hyperglycemia circumstance. MAE activates AMPK and its targets in vitro and in vivo . MAE shows protective effects on pancreas damage in db/db mice. Abstract: This study evaluated the capacity of mulberry anthocyanin extract (MAE) on oxidative damage alleviation and related protein expression regulation in HepG2 cells and type 2 diabetic mice.  In vitro, exposure of cells to high glucose and palmitic acid resulted in ROS and O2 − accumulation, mitochondria numbers and MMP decreases, which could be partly recovered by MAE. However, beneficial effects of MAE on insulin resistance improvement including glucose consumption and uptake increases were impaired by Compound C. In vivo, supplementation of MAE markedly mitigated pancreatic injuries which might be associated with autophagy stimulation. After MAE intervention, an upregulation of AMPK phosphorylation accompanied by ACC and mTOR downregulation, alterations of p38-MAPK and PGC-1α expressions were found in insulin sensitive tissues. Therefore, these findings suggest that MAE has potential benefits on protecting hepatocytes against oxidative stress during hyperglycemia in HepG2 cells and improving dysfunction in diabetic mice via regulation of AMPK/ACC/mTOR pathway.